Diode-pumped intracavity yellow–green Raman laser at 560 nm with sum-frequency-generation☆. (March 2015) - Su, Fufang; Zhang, Xingyu; Wang, Wei tao; Cong, Zhenhua; Shi, Men; Han, Peigao; Wu, Wendi; Yang, Xiuqin; Ma, Lili
Abstract: By using Nd:YVO4 as the gain medium and the Raman medium simultaneously, KTP as the sum-frequency crystal, the actively Q-switched operation of the 560 nm Raman laser by sum-frequency generation was realized. The output characteristics versus the incident pump power and the pulse repetition rates were investigated. At a pulse repetition rate of 40 kHz an average power up to 0.9 W was obtained with the incident pump power of 13.7 W, corresponding to a conversion efficiency of 6.6% with respect to the diode laser input power. Highlights: The Nd:YVO4 /KTP sum-frequency actively Q-switched Raman laser is studied in detail. The output characteristics versus the pump power and the pulse repetition rates were investigated. The maximum Stokes pulse energy is 29.5 μJ at the incident pump power of 13.7 W. The obtained maximum average power is 0.9 W at the incident pump power of 13.7 W.